New names for Ilex and Ilexpollenites (Aquifoliaceae), extant and fossil. Notulae Systematicae ad Palaeofloram Europaeam spectantes II. Aquifoliaceae - Doweld, Alexander B. (Phytotaxa, 2019)
New names are proposed for the fossil European Tertiary species of Ilex (The Palaeoflora Europaea Project): Ilex angustifolioides nom. nov., Ilex boulayi nom. nov., Ilex friedrichii nom. nov., Ilex latifolioides nom. nov., and Ilex opacina nom. nov. Ilex integrifolia Baikovskaja from Central Asia is renamed Ilex aschutassica nom. nov. (non extant Ilex integrifolia Hort. ex Vilmorin and Ilex integrifolia Chapman ex Knowlton). Ilex mormonica nom. nov. of North America is proposed in place of Ilex acuminata Becker (fossil) non Ilex acuminata Willdenow (extant). Ilex polarica nom. nov. from Greenland is validated in place of Ilex macrophylla Heer (fossil) non Ilex macrophylla Blume (extant). Ilex fortunensis Hahn (extant) is renamed Ilex hahnii nom. nov. (not fossil Ilex fortunensis van der Burgh). Ilex subrotunda sp. nov. is validated instead of the previously invalidly published I. ohashii, lacking holotype designation when published. Fossil-species of Ilex, based on the dispersed pollen, Ilex major, I. colchiciformis, I. hyrcaniformis, I. macroclavata, I. tener, are transferred to the pollen fossil-genus Ilexpollenites. Fossil-species based on leaves, Ilex artocarpidioides and Ilex ovata are segregated into a separate genus Celastrilex gen. nov. Fossil-species Ilex pseudostenophylla, based on leaf remains, is excluded from Ilex and placed into a new fossil-genus Frangulops gen. nov. The following new combinations are proposed: Ilex ulmacea comb. nov., Ilexpollenites: Ilexpollenites major comb. nov., I. colchiciformis comb. nov., I. hyrcaniformis comb. nov., I. macroclavata comb. nov., I. tener comb. nov.; Celastrilex artocarpidioides, C. populifolia; Frangulops pseudostenophylla. Furthermore, Celastrus ulmaceus is neotypified; Ilex acuminata Saporta, I. berberidifolia, I. mougeotii and I. rueminiana are lectotypified.